2022
DOI: 10.1039/d1ra08890d
|View full text |Cite
|
Sign up to set email alerts
|

Integration detection of mercury(ii) and GSH with a fluorescent “on-off-on” switch sensor based on nitrogen, sulfur co-doped carbon dots

Abstract: NS-CDs are employed as a sensitive sensor for the integration detection of Hg2+ and GSH. Hg2+ effectively quenching the fluorescence by static quenching. GSH is able to recover the fluorescence owing to the stronger binding between Hg2+ and GSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…As shown in Figure S3a, the transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) image results show that NCQDs are uniformly distributed spherical carbon particles with a lattice spacing of 0.21 nm, corresponding to the (001) diffraction plane of sp 2 graphite carbon . The optical properties of NCQDs are studied, as shown in Figure S3b–d, UV–vis spectra peaks of NCQDs at 240 and 331 nm corresponding to the CC bond (π → π*) and CO/CN bond (n → π*), respectively. , The X-ray diffraction (XRD) profile of NCQDs shows an obvious wide peak at 22.6° (Figure S4a), corresponding to a graphite-like structure. , In addition, the composition and structure of NCQDs were further characterized and the Raman spectroscopy were studied (Figure S4b). Two obvious peaks corresponded to the typical D-band and G-band, and the I D / I G value is only 0.45, which suggests NCQDs have a high graphitization degree .…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure S3a, the transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) image results show that NCQDs are uniformly distributed spherical carbon particles with a lattice spacing of 0.21 nm, corresponding to the (001) diffraction plane of sp 2 graphite carbon . The optical properties of NCQDs are studied, as shown in Figure S3b–d, UV–vis spectra peaks of NCQDs at 240 and 331 nm corresponding to the CC bond (π → π*) and CO/CN bond (n → π*), respectively. , The X-ray diffraction (XRD) profile of NCQDs shows an obvious wide peak at 22.6° (Figure S4a), corresponding to a graphite-like structure. , In addition, the composition and structure of NCQDs were further characterized and the Raman spectroscopy were studied (Figure S4b). Two obvious peaks corresponded to the typical D-band and G-band, and the I D / I G value is only 0.45, which suggests NCQDs have a high graphitization degree .…”
Section: Results and Discussionmentioning
confidence: 98%
“…51,52 The X-ray diffraction (XRD) profile of NCQDs shows an obvious wide peak at 22.6°(Figure S4a), corresponding to a graphite-like structure. 53,54 In addition, the composition and structure of NCQDs were further characterized and the Raman spectroscopy were studied (Figure S4b). Two obvious peaks corresponded to the typical D-band and G-band, and the I D /I G value is only 0.45, which suggests NCQDs have a high graphitization degree.…”
Section: Synthesis and Characterization Of Ncqds As Shown In Figurementioning
confidence: 99%
“…The HRTEM image of F-NCDs showed that the particles were approximately spherical (Figure 2a), with size distribution between 0.7~3.5 nm, and the average size of 2.0 nm (Figure 2b). The XRD spectrum of F-NCDs showed that there was an obvious diffraction peak around 23° (Figure 2c), which corresponded to the amorphous structure [21,22] . FTIR spectrum of F-NCDs displayed that a typical wide absorption band…”
Section: Characterization Of F-ncdsmentioning
confidence: 99%
“…According to previous studies, element doping can effectively improve the optical properties of CQDs in this aspect, 20,21 and the extraneous element in CQDs can also provide a stronger response to Hg(II) through the interaction of coordination/ complexation, photoinduced electron transfer (PET), ion binding or aggregation effects. [22][23][24][25][26][27] In this work, a new complex of carbon dots doped with nitrogen and silicon (N,Si/CQDs) was prepared from folic acid (FA) and N- [3-(trimethoxysily)propyl]-ethylenediamine (DAMO). FA molecule provides the functional groups of -NH 2 and -COOH, which are deemed as the efficacious components for Ndoping in CQDs to improve the quantum yield.…”
Section: Introductionmentioning
confidence: 99%